Letramento e alfabetização: as muitas facetas - Magda Soares (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2004)
Describes how the concepts of literacy and initial reading instruction developed in Brazilian education throughout the last two decades, characterising this development as a progressive invention of the word and concept of literacy and a concomitant dis-invention of the concept of initial reading instruction, which lost its specific characteristics, bringing about a new type of school failure: the serious reading and writing difficulties among students at advanced levels of schooling. The text discusses the causes of this phenomenon and stresses the need to distinguish clearly between initial reading instruction and literacy, so that each process is seen as specific and, at the same time, as associated with and dependent on the other. The present situation is characterised as an attempt to re-invent initial reading instruction, meaning not a turning back to past methodologies, but as a recovery of the distinctive features of the initial reading instruction process in its multiple facets, guaranteeing at the same time its integration with the literacy process.